Persepsi Ulama Kota Langsa Terhadap Kepemimpinan Wanita ( Studi Kasus Pilkada Walikota Langsa ) - Muhajir, Muhajir; fakhrurrazi, Fakhrurrazi (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2020)
In this day and age, women take part in almost all fields of activity or work, including in regional head elections. The advantage of a man over a woman is that he has the ability to think, which is why he gives birth to courage, strength and the ability to overcome various difficulties. Meanwhile, women are more sensitive and emotional. In reality and current reality shows that the view of the greatness of men and the weakness of women from the intellectual and professional side. The purpose of this study is to analyze the perceptions of the Ulama Kota Langsa on the leadership of women in the local elections for the mayor of the City of Langsa and to identify the factors that influence the different perceptions of the Ulama Kota Langsa about the leadership of women in the City of Langsa. The method used in this study is a qualitative descriptive research method that produces data in the form of written and spoken words from the subject under study. The main target of this research is the ulama of Langsa city. Data collection techniques are observation, in-depth interviews and documentation. The data validity used is data triangulation technique. Data analysis includes 4 things, namely data collection, data reduction, data presentation, and drawing conclusions. The result of this research is that the Ulama of Langsa city show that women can be leaders in the public sector, but the concept of understanding ideal leadership in Islamic teachings which they understand places men as the top priority to become leaders. Women are deemed to be allowed to become leaders if there are no men who are able to hold the position or the woman has more talent or expertise than the existing men.